Public State Services for Merchants in the Islamic East in the Book Masalik al-Ibsar fi Mamlik al-Amsar by Ibn Fadl Allah al-Amri, who Died 749 AH / 1349 AD - Salman , Amer Adnan; Mohammed , Saddam Jassim (Journal of Ecohumanism, 2025)
Commercial activity in the countries of the Islamic East required care for merchants and trade caravans and hospitality through the efforts made by the Arab Islamic state and the rulers of the provinces in the East to eliminate dangers, achieve political and administrative stability, establish security, conclude agreements with countries and kingdoms neighboring the East, and establish guard posts on the roads. In addition to that, there was the nature of the people of the East who were accustomed to welcoming and caring for guests and trade caravans passing through the cities and regions of the Islamic East. Many ribats and inns emerged in the cities, and these ribats became rest stops for merchants and travelers to stock up on what they needed for themselves and their animals for long journeys, in addition to what they found of security, reassurance, and peace during the buying, selling, and banking operations.